Kinetics of high density functional polymer nanocomposite formation by tuning enthalpic and entropic barriers. Issue 5 (12th January 2022) - Swain, Aparna; Das A, Nimmi; Chandran, Sivasurender; Basu, J. K.
Abstract : High density functional polymer nanocomposites (PNCs) with a high degree of dispersion have recently emerged as novel materials for various thermo-mechanical, optical and electrical applications. Abstract : High density functional polymer nanocomposites (PNCs) with high degree of dispersion have recently emerged as novel materials for various thermo-mechanical, optical and electrical applications. The key challenge is to attain a high loading while maintaining reasonable dispersion to attain maximum possible benefits from the functional nanoparticle additives. Here, we report a facile method to prepare polymer grafted nanoparticle (PGNP)-based high density functional polymer nanocomposites using thermal activation of a high density PGNP monolayer to overcome entropic or enthalpic barriers to insertion of PGNPs into the underlying polymer films. We monitor the temperature-dependent kinetics of penetration of a high density PGNP layer and correlate the penetration time to the effective enthalpic/entropic barriers. The experimental results are corroborated by coarse-grained molecular dynamics simulations. Repeated application of the methodology to insert nanoparticles by appropriate control over temperature, time and graft-chain properties can lead to enhanced densities of loading in the PNC. Our method can be engineered to produce a wide range of high density polymer nanocomposite membranes for various possible applications including gas separation and water desalination.